Development of a web-based water supply complaint management system / Ema Kulata Anak Merang, Alif Faisal Ibrahim and Muhammad Nabil Fikri Jamaluddin - Merang, Ema Kulata; Ibrahim, Alif Faisal; Jamaluddin, Muhammad Nabil Fikri (UiTM Cawangan Perlis, 2022)
Every neighbourhood must have access to clean water supply. Disturbances in the water supply may have negative effects on both the economy and public health. Currently there are various methods of filing a complaint to the local water supply distributor. Improper management of these complaints lead to slow responses to affected area, causing displeasure among the users. The aim of the research is to design and develop a web-based Water Supply Complaint Management System to assist users to file complaints related to water supply issues. The system was also designed to assist local authorities or water supply distributor company to properly manage complaints to act quickly. User acceptance testing is used to evaluate the proposed system after it has undergone numerous functional tests. The system was developed using the System Development Life Cycle (SDLC) and the waterfall model was chosen for the methodology. Thirty respondents from Sibu, Sarawak, were chosen to participate in the testing phase and were asked to complete questionnaires that were divided into four categories, including user interface satisfaction, ease of use, usability, and functionality. According to the results of the evaluation, most of the respondents gave positive feedbacks towards the overall functionality of the proposed system. Therefore, it is hoped that all features provided by the proposed system will benefit all users, particularly those who frequently have water supply related issues in their community.